2019
DOI: 10.1039/c9ta02035g
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the synthesis of uniform electron-deficient Pd clusters for superior hydrogen production from formic acid

Abstract: The superior additives-free dehydrogenation of formic acid for hydrogen production by uniform electron-deficient Pd clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…3 [55] HCOONa in H 2 O at 80 °C 308 000 25 700 98 000 0.96 0.34 4 [56] NA in H 2 O at 60 °C 5 000 000 1900 98 000 0.06 12.18 5 [57] NA in H 2 O at 80 °C 2 400 000 171 000 125 000 0.16 0.25 6 [58] HCOONa 11 [64] NEt 3 in dioxane at 40 °C 100 000 653 168 000 5.09 108.99 12 [65] LiBF 4 in dioxane at 80 °C 983 642 196 728 g) 11 000 0.03 0.03 13 [66] HCOONa in neat HCOOH at 90 °C 2 160 000 13 320 e) 90 000 0.12 2.07 14 [67] NA in neat HCOOH at 95 °C 1 701 150 3067 158 000 0.28 15.51 15 [68] NA in H 2 O at 50 °C NA h) 18 625 f) 28 000 1.69 1.45…”
Section: Homogeneous Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…3 [55] HCOONa in H 2 O at 80 °C 308 000 25 700 98 000 0.96 0.34 4 [56] NA in H 2 O at 60 °C 5 000 000 1900 98 000 0.06 12.18 5 [57] NA in H 2 O at 80 °C 2 400 000 171 000 125 000 0.16 0.25 6 [58] HCOONa 11 [64] NEt 3 in dioxane at 40 °C 100 000 653 168 000 5.09 108.99 12 [65] LiBF 4 in dioxane at 80 °C 983 642 196 728 g) 11 000 0.03 0.03 13 [66] HCOONa in neat HCOOH at 90 °C 2 160 000 13 320 e) 90 000 0.12 2.07 14 [67] NA in neat HCOOH at 95 °C 1 701 150 3067 158 000 0.28 15.51 15 [68] NA in H 2 O at 50 °C NA h) 18 625 f) 28 000 1.69 1.45…”
Section: Homogeneous Catalysismentioning
confidence: 99%
“…[77b] Interestingly, Ye et al have employed amine-modified SiO 2 , and graphene oxide (Pd@NH 2 -SiO 2 @NH 2 -GO, 15) for additive-free FA dehydrogenation to achieve a TOF of 18625 h −1 at 50 °C. [68] Such improved performance was attributed to NH 2 functionalities, which result in the formation of electron-deficient Pd clusters and also serve as proton reservoirs for dehydrogenation of FA.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…The production of hydrogen from FA proceeds via a dehydrogenation reaction (HCOOH ↔ H 2 + CO 2 ) that can be promoted by both homogeneous [ 12 , 13 ] and heterogeneous [ 14 , 15 , 16 ] catalysts, the latter being the preferred choice because of advantages associated with their use. The heterogeneous catalysts used in this reaction are frequently based on Pd nanoparticles supported on materials of diverse composition [ 6 , 17 , 18 , 19 , 20 , 21 , 22 ], with carbon materials being some of the most common supports [ 7 , 23 , 24 ]. Despite the vast literature reporting on Pd-carbon-based catalysts for the dehydrogenation of FA, most of the studies are aimed at optimizing the properties of the catalytic active phase (i.e., particle size [ 23 , 25 , 26 ], composition [ 17 , 27 , 28 , 29 , 30 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the homogeneous catalysts based on Ir, Ru, and Fe organometallic complex usually have great catalytic activity and selectivity, while gold 25 , Platinum 26 , and palladium 4 well known heterogeneous catalysts used in the decomposition of FA. However, some reports have shown that nanostructure with base Pd such as Au 0.5 Pd 0.5 /NH 2 -N-rGO 27 , Pd-MIL-125 28 , Pd 1 Au 1 /30-LA 29 , AP-SiO 2 @PDA-NGO@Pd 30 , PdAu-MnOx/N-SiO 2 31 , CrAuPd/N-SiO 2 32 , IrPdAu/NH 2 -SBA-15 33 , Ag 0.2 Au 0.4 Pd 0.4 /rGO 34 , Au@Pd/UiO-66(Zr x Ti y ) 35 , Au–Pd/MIL-101 36 , and PdCoNi/TiO 2 37 , can efficiently decomposed FA under neat condition. Recently, our research group explored the catalytic application of Pd@Cu-MOF 38 and Pd@Cr-MOF 39 with open metal sites as an ideal Pd-catalyst for H 2 generation from FA in neat condition.…”
Section: Introductionmentioning
confidence: 99%